2021
DOI: 10.1155/2021/6664591
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Agomelatine Softens Depressive‐Like Behavior through the Regulation of Autophagy and Apoptosis

Abstract: Depression is a common and disabling mental disorder with high recurrence rate. Searching for more effective treatments for depression is a long-standing primary objective in neuroscience. Agomelatine (AGO) was reported as an antidepressant with unique pharmacological effects. However, its effects and the underlying mechanism are still unclear. In this study, we sought to evaluate the antidepressant effects of AGO on the chronic restraint stress (CRS) mouse model and preliminarily investigate its effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…This antiapoptotic gene was induced only by the drug, both in the basal condition as well as after stress exposure. Bcl-xL is known to have a pronounced neurotrophic effect supporting neuronal survival [ 45 ], and its modulation by the pharmacological treatment is in agreement with the reported antiapoptotic properties of agomelatine itself [ 46 , 47 ] and of other antidepressants [ 48 , 49 , 50 ]. Thus, in addition to the anti-inflammatory properties, agomelatine also possesses a neuroprotective role that might act together to normalize the stress-induced activation of the IL-6 pathway and its deleterious effects.…”
Section: Discussionsupporting
confidence: 68%
“…This antiapoptotic gene was induced only by the drug, both in the basal condition as well as after stress exposure. Bcl-xL is known to have a pronounced neurotrophic effect supporting neuronal survival [ 45 ], and its modulation by the pharmacological treatment is in agreement with the reported antiapoptotic properties of agomelatine itself [ 46 , 47 ] and of other antidepressants [ 48 , 49 , 50 ]. Thus, in addition to the anti-inflammatory properties, agomelatine also possesses a neuroprotective role that might act together to normalize the stress-induced activation of the IL-6 pathway and its deleterious effects.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, cumulative HPA axis activities have been assessed based on hair cortisol levels, and the results suggest that stress and depressive symptoms are related to high cortisol levels [17,18]. Furthermore, in stress-induced depression model animals, the blood corticosterone concentration increased, and the brain BDNF level decreased, with resulting inflammation in the hippocampus and prefrontal cortex [19][20][21], while chronic administration of corticosterone to rodents induced a similar pathogenesis [22,23]. These results suggest that HPA axis-mediated dysregulation of stress response (i.e., HPA axis hyper-activation) contributes to the development and progress of depressive symptoms.…”
Section: Abnormal Stress Responsementioning
confidence: 99%
“…Therefore, autophagy is considered to be an important part of the stress response (Kumsta et al, 2017). A growing number of clinical studies and animal models of depression have shown that the abnormal expressions of ATG genes and proteins are involved in the pathophysiology of MDD and the mechanism of antidepressants, including LC3, P62, and Atg7 (Shu et al, 2019;Zhang et al, 2020;Chen et al, 2021;Scaini et al, 2021;Sakai et al, 2022). Moreover, in our previous study, we constructed a diagnostic model using ATGs and found that a model of four ATGs (PDK4, NRG1, EphB2, and GPR18) had a good capacity to distinguish MDD patients from controls (He et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ezh2 is a histone-lysine N-methyltransferase enzyme (Borbone et al ., 2011), which played an important role in the epigenetic silencing of target genes (Huqun et al ., 2012). Some studies have found that Ezh2 participated in the process of autophagy by regulating ATG proteins, such as LC3, Atg7, Beclin1, P62, and Stat3 (Li et al ., 2018; Ma et al ., 2018; Chen et al ., 2019, 2020). To our knowledge, only one study has explored the association between Ezh2 and depression, which found that Ezh2 was involved in the susceptibility to depression-like behaviors and neuroinflammation in the hippocampus and prefrontal cortex in different aged mice (Wang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%